Sekolah Pasar Modal Level I 2018 Pada Masyarakat Arsopura, Kabupaten Keerom - Antonius H.C. Wijaya (UNIVERSITAS CENDERAWASIH, 2018)
Becoming an investor at the present time is not difficult because through one of the programs from the investment gallery that has collaborated with the existing universities in Indonesia is one of the media to attract students to become young investors. Not just students, through village programs saving shares from this gallery which gives equal opportunities to villagers to become investors. Therefore, community service activities were carried out in the village of Arsopura, Keerom Regency, Papua Province which aims to conduct education and the introduction of capital markets to rural communities to also be involved as capital market players. The final result of this activity is that there were 20 residents who directly open their share accounts and can immediately become an investor.